Exploring literacy barriers : Analyzing the reading challenges and educational inequities faced by immigrant children in Finland - Virtanen, Joanna (My University, 2025)
This thesis examines the educational disparities and literacy barriers faced by immigrant children in Finland, with a focus on different variables which affect their reading challenges. Since the early 1990s, the number of immigrants has increased drastically, which has had an immense effect on Finland's educational environment and required institutions to adjust to a diverse student body. This thesis, which brings together the ideas from current research, highlights socioeconomic status, language proficiency, and cultural dynamics as important elements influencing first-generation immigrant students' literacy learning. This study examines how immigrant children commonly face a variety of difficulties, such as restricted access to learning materials, disruptions in their prior education and the influence of their home language affecting their schooling. The study also emphasises how crucial school support is and how crucial it is to use culturally sensitive teaching methods in order to improve language acquisition and increase academic achievement. The findings indicate how important it is to address institutional and structural issues in the educational system in order to improve equal opportunities for immigrant children. The main objective of this thesis is to provide information for policy recommendations that would improve educational outcomes for Finnish immigrant children and create a more inclusive environment for learning.

Tämä opinnäytetyö tutkii maahanmuuttajalasten kokemia koulutuksellisia eroja ja lukutaidon esteitä Suomessa, keskittyen eri muuttujien vaikutuksiin heidän lukemisvaikeuksiinsa. 1990-luvun alusta lähtien maahanmuuttajien määrä on kasvanut huomattavasti, mikä on vaikuttanut merkittävästi Suomen koulutukselliseen ympäristöön ja vaatinut instituutiolta sopeutumista moninaisiin oppijoihin. Tämä opinnäytetyö kokoaa yhteen ajankohtaisten tutkimusten ideoita ja korostaa sosioekonomista asemaa, kielitaitoa ja kulttuurisia tekijöitä ensisukupolven maahanmuuttajaoppilaiden lukutaidon oppimiseen vaikuttavina tärkeinä elementteinä. Tutkimus tarkastelee, kuinka maahanmuuttajalapset kohtaavat usein monenlaisia vaikeuksia, kuten rajoitettua pääsyä oppimateriaaleihin, keskeytyksiä aiemmassa koulutuksessaan, sekä kotikielen vaikutusta heidän koulunkäyntiinsä. Tutkimus korostaa myös koulun tuen merkitystä ja kulttuurisesti herkän opetuksen käyttämisen tärkeyttä kielen omaksumisen parantamisessa ja akateemisen saavutuksen lisäämisessä. Tulokset osoittavat, kuinka tärkeää on puuttua koulutusjärjestelmän institutionaalisiin ja rakenteellisiin ongelmiin parantaakseen tasa-arvoisia mahdollisuuksia maahanmuuttajalapsille. Opinnäytetyön päätavoitteena on tarjota tietoa politiikkasuosituksille, jotka parantaisivat maahanmuuttajalasten koulutuksellisia tuloksia Suomessa ja loisivat osallistavamman oppimisympäristön.
Keywords: Educational inequity, literacy, integration, Finland, immigrant students, koulutuksellinen eriarvoisuus, lukutaito, integraatio, Suomi, maahanmuuttajaoppilaat